Intervention in teaching reading in a foreign language: : development of divergent thinking and ambiguity tolerance - Gadušová, Zdenka; Pavlíková, Martina; Havettová, Romana (Journal of Education Culture and Society, 2021)
Aim. The paper presents partial results of research aimed at the development of foreign language reading comprehension using the specially developed intervention programme. Concept. The English Reading Comprehension Intervention Program has been developed within the research project Support for reading literacy in the mother tongue and foreign language. It consists of 10 intervention units and is based on 10 identified predictors, the conscious development of which contributes to students’ success in reading comprehension. Methodology. Assumptions presented in the paper are based on the cognitive theory of learning, identifying which cognitive processes precede the predictors with the greatest share of influence, and which higher cognitive processes follow them. Based on these scientific hypotheses and research results, we have determined the predictors positively influencing reading comprehension and worth intervening in the process of development of reading comprehension.Results and conclusions. In the paper, the English Reading Comprehension Intervention Program for B1 level of language proficiency is introduced, with both the content and methodology of its class application described. The predictors of divergent thinking and ambiguity tolerance are discussed in detail as the presented example of the intervention unit is focused on their development. Originality. While intervention programmes are not a new phenomenon, the recently developed reading comprehension intervention programmes for foreign languages are a valuable contribution to teaching foreign language reading comprehension in primary and secondary schools. They provide foreign language teachers with ready-made materials, which can be immediately used in their classes and will contribute to better learning results of their students.